STUDI TENTANG PARTISIPASI PADA KOPERASI MAHASISWA AMANAH UNIVERSITAS BHINNEKA PGRI (PEMBINA, PENGAWAS, PENGURUS DAN ANGGOTA) - Safitriana, Hana; Subiyantoro, Hari (Jurnal Ekonomi dan Pendidikan, 2023)
The aim of the study was to determine the participation of coach, supervisor, administrators and members in the Amanah Student Cooperative. This type of research is qualitative. Based on the research, the results were obtained: 1) The participation of the coach in the Amanah Student Cooperative, namely providing advice or directions to the management, but the suggestions given by the coache have not been able to meet the needs in solving problems; 2) Participation of supervisors, namely supervising the performance of cooperative management which is carried out as needed in 2 ways, namely open supervision and closed supervision; 3) Management participation in the Amanah Student Cooperative has not been able to support the success of the cooperative; 4) Participation of members in the Amanah Student Cooperative only contributes actively to the utilization of services provided by the cooperative so that it can be said that members have low participation in cooperatives. In this case, it can be concluded that the participation of both coach, supervisor, administrators and members in the Amanah Student Cooperative is considered very low so that it has not been able to create a healthy and independent cooperative